GAMBARAN KARAKTERISTIK WANITA USIA SUBUR (WUS) YANG MELAKUKAN PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT (IVA) DI PUSKESMAS KARANGANYAR - Pangesti, Nova ari; aminoto, cokro; laela, nur (LPPM STIKES MUHAMMADIYAH GOMBONG, 2012)
Cervical cancer is a malignant tumor that attacks the cervix causedby HPV (Human Papilloma Virus). Health Profile in 2010 states that thepercentage of cervical cancer is 19.70% per 10,000 populations. Forearly detection of cervical cancer is through examination of IVA or inIndonesian means Visual Inspection with Acetic Acid. IVA is a newmethod of early detection of cervical cancer by applying acetic acid(vinegar) into the cervix which is relatively cheap and effective. Data inthe Community Health Center of Karanganyar until 2010 obtained thenumber of 137 patients were positive with IVA. The number of patientswho have already done colposcopy were 32 patients, kreoterapy were 137patients and biopsy were 4 patients.This study was to determine the characteristics of fertile agewomen who had done (IVA) in Community Health Centre ofKaranganyar.This research was conducted using descriptive type of observationalresearch. The total sample were 76 respondents that taken by usingstratified random sampling technique for fertile age women who haddone IVA in the Community Health Center of Karanganyar in 2010.The data were collected by using questionnaires. Data analysis wasperformed using SPPS (Statistical Package for Social Science) version16.0.The results of 76 respondents showed that most respondentswere in the range of 30-40 years old (52.6%). The highestpercentage for the educational background were for primary/secondary education or the equal schools were 76.3%. The highestlevel of knowledge was in the enough category (40.8%). In marital statuscategory, the highest percentage was in one time married (88.2%),the highest percentage parity was responden that have two children,based on the use of contraceptive usage, the highest percentage usedinjective contraception (26.3%). Mostly the respondents indicatednegative with IVA (92.1 %).Keywords: Cervical Cancer, IVA, Characteristics of Fertile Age Women